Egipski kontekst wynalezienia alfabetu (inskrypcje z Serabit Al-Chadim oraz Wadi Al-Hôl) - Nowogórski, Przemysław (Saeculum Christianum. Pismo Historyczne, 2016)
The article presents the beginnings of alphabetic writing in Sinai (Serabit al-Chadim) in the context of the Egyptian hieroglyphic writing and the subsequent early alphabetic inscriptions from Wadi al-Hôl (Egypt) and Wadi Arava (Israel). In the light of the present state of research it can be concluded that the oldest alphabet (type: abgad) was established Semites working in the copper mines in Sinai under the rule of Egypt, probably in the nineteenth century BC. Direct effects on Semitic alphabetic writing had Egyptian hieroglyphs. Discovered in recent years alphabetic inscriptions in the Wadi al-Hôl and Wadi Arava turned out to be younger than the Sinaic inscriptions and are another element in the early development of alphabetic writing